Son las aerolíneas latinoamericanas más ineficientes? Estimaciones con fronteras estocásticas - Gustavo Ferro; Pablo Daniel Monterubbianesi (Universidad del Centro de Estudios Macroeconómicos de Argentina (UCEMA), 2016)
– This study aims to answer the following questions: which is the average efficiency level in passenger transportation of an airline sample operating in the Western Hemisphere? How do Latin American airlines perform in comparison with American ones? Are there technical efficiency differences between airlines of the sample? Why? To answer, we employ stochastic frontier methods and we add to precedent studies the usage of an ample set of alternative techniques and the specific consideration to Latin American airlines.
Keywords: L93; C19; 330; stochastic frontiers; airlines; efficiency